The Effectiveness of Schema Therapy on the Mental Health and Emotional Self-regulation of Depressed Women in Bandar Abbas City - Zohreh Jafari; Mahin Askari; Nooshin Taghinejad (Iranian Journal of Educational Research)
Objective: Schema therapy is a therapeutic approach that focuses on identifying and changing negative patterns of thinking and behavior that contribute to emotional distress. This study aimed to investigate the impact of schema therapy on the mental health and emotional self-regulation of depressed women in Bandar Abbas City. Methods: The research design was a quasi-experimental pretest-posttest with a control group. The statistical population of this research was all the women involved with the issue of mental illness disorder and depression who referred to the counseling centers of Bandar Abbas in 2022-2023. In this case, 30 participants were selected by purposeful sampling and randomly replaced in two equal groups of 15 people (one experimental group and one control group). In this study, a questionnaire was used as the main research tool. The questionnaire included several validated measures, namely the Beck Depression Inventory (BDI), the Emotion Regulation Questionnaire (ERQ), the Schema Therapy Inventory (STI), and the General Health Questionnaire (GHQ). Results: After eight sessions of schema therapy in the experimental group, the questionnaires were given to the participants again. The data collected from these questionnaires was then graphed to visualize the results. Analysis of the graphed data revealed a therapeutic efficacy of 62% and 63% for the first and second hypotheses, respectively. Conclusions: The study found that schema therapy was effective in reducing mental health disorders and improving emotional self-regulation in depressed women. This suggests that schema therapy can be a valuable intervention for improving mental health and emotional well-being in depressed women.